2008
DOI: 10.1016/j.prostaglandins.2008.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized glycerophosphocholines as biologically active mediators for ultraviolet radiation-mediated effects

Abstract: Ultraviolet light radiation (UVR) has profound effects upon human skin. Yet, the exact targets for UVR are unclear. Inasmuch as UVR is a known pro-oxidative stressor, one potential target for UVR could be oxidatively modified glycerophosphocholines (GPC). Importantly, recent studies demonstrate that these oxidized GPCs (ox-GPC) are potent agonists for the platelet-activating factor receptor and peroxisome proliferator-activated receptor gamma. This review discusses these new biologically active lipids and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 101 publications
(140 reference statements)
2
48
0
Order By: Relevance
“…When this reaction is performed in the presence of PAPC vesicles, bioactive oxidized phospholipids are formed, and these can also be isolated from cultured fibroblasts that were exposed to PBS supplemented with Rose Bengal and exposed to visible light [13]. A large number of oxidation products is formed upon in-vitro UVA irradiation of phospholipids containing arachidonic-or docosahexaenoic acid, confirming that the immediate generation of many bioactive oxidation products of PL that we and others observed in the skin after UVR does not necessarily require UV-induced enzymatic activity [50][51][52]. The observed increase in 8-isoprostane in the supernatants of Nrf2 deficient and supplemented fibroblasts is not only a good independent indicator of enhanced oxidative stress in these cells but also suggests that synthesis and secretion of 8-isoprostane (which is discarded via the urine) is a strategy of cells to reduce the burden that PUFA pose under oxidative stress.…”
Section: Non-enzymatic Generation Of Uv-induced Lipid Mediatorssupporting
confidence: 73%
See 1 more Smart Citation
“…When this reaction is performed in the presence of PAPC vesicles, bioactive oxidized phospholipids are formed, and these can also be isolated from cultured fibroblasts that were exposed to PBS supplemented with Rose Bengal and exposed to visible light [13]. A large number of oxidation products is formed upon in-vitro UVA irradiation of phospholipids containing arachidonic-or docosahexaenoic acid, confirming that the immediate generation of many bioactive oxidation products of PL that we and others observed in the skin after UVR does not necessarily require UV-induced enzymatic activity [50][51][52]. The observed increase in 8-isoprostane in the supernatants of Nrf2 deficient and supplemented fibroblasts is not only a good independent indicator of enhanced oxidative stress in these cells but also suggests that synthesis and secretion of 8-isoprostane (which is discarded via the urine) is a strategy of cells to reduce the burden that PUFA pose under oxidative stress.…”
Section: Non-enzymatic Generation Of Uv-induced Lipid Mediatorssupporting
confidence: 73%
“…Several prostaglandins and enzymatic n-3 PUFA metabolites are regulators of the PPAR transcriptional coactivators which regulate skin homeostasis and UV responses [62], and PPARG apparently counteracts UVB induced inflammation [63]. Upon UV exposure, the PPARG agonist 1-alkyl-2-azelaoyl-PC can form non-enzymatically, is active when still esterified to the PL [52] but can also be cleaved by PLA2 to release free azelaic acid [64]. In this study we have detected 1-acyl-2azelaoyl-PC to be formed by UV and increased upon DHA supplementation.…”
Section: Signaling Pathways Utilized By Lipid Photoproductsmentioning
confidence: 99%
“…A second mechanism for Ox-GPC generation appears to be the direct absorption of UVB irradiation by lipids and is immediate (28,29,40). Although GPCs do not absorb light in the UVB range, we have shown that Ox-GPCs do absorb in this range (29). Thus, small amounts of Ox-GPCs that are found in cells at any one time can serve as targets for UVB irradiation.…”
Section: Discussionmentioning
confidence: 74%
“…First, UVB irradiation can generate the delayed production of ROS through a process involving NADPH and the epidermal growth factor receptor (40,62,63). A second mechanism for Ox-GPC generation appears to be the direct absorption of UVB irradiation by lipids and is immediate (28,29,40). Although GPCs do not absorb light in the UVB range, we have shown that Ox-GPCs do absorb in this range (29).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation